2016
DOI: 10.1108/ijwhm-09-2015-0054
|View full text |Cite
|
Sign up to set email alerts
|

Work-related wellbeing in UK prison officers: a benchmarking approach

Abstract: PURPOSE: This paper utilises a benchmarking approach to examine the wellbeing of UK prison officers.APPROACH: The Health and Safety Executive (HSE) Stress Indicator Tool is widely used in the UK to assess key psychosocial hazards in the workplace encompassing demands, control, support from managers and co-workers, relationship quality, role and change management.This study utilises this approach to examine the extent to which a sample of UK prison officers meets the HSE recommended minimum standards for the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
1
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(79 citation statements)
references
References 59 publications
(94 reference statements)
3
65
1
10
Order By: Relevance
“…Insight into the types of illness that are viewed as legitimate or illegitimate causes for sickness absence by officers and managers should also be examined. There is evidence that the mental health of prison officers is poorer than people working in other safety-critical jobs, but disclosure is frequently stigmatised (Kinman et al, 2016). Research findings indicate that mental health problems are a particularly common reason for presenteeism (Cooper & Dewe, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insight into the types of illness that are viewed as legitimate or illegitimate causes for sickness absence by officers and managers should also be examined. There is evidence that the mental health of prison officers is poorer than people working in other safety-critical jobs, but disclosure is frequently stigmatised (Kinman et al, 2016). Research findings indicate that mental health problems are a particularly common reason for presenteeism (Cooper & Dewe, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Unsurprisingly, studies have found that prison officers have one of the highest rates of work-related stress, illness and injury of all occupational groups (Dugan, Farr, Namazi, et al, 2016;Global Prison Trends, 2016). The incidence of burnout and post-traumatic stress disorder is greater than that found in other safety-critical occupations (Denhof & Spinaris, 2013) and the risk of sleep disorders, depression, anxiety and suicidal ideation is also comparatively high (James, Todak, & Best, 2017;Kinman, Clements, & Hart, 2016;Walker, Jackson, & Egan, 2015). Research conducted with correctional staff in several countries has found that negative health behaviours, such as low physical activity, poor diet and problem drinkin,g are particularly common and they are at particular risk of cardiovascular disease, stomach ulcers and musculoskeletal disorders (Campos, Schneider, Bonafe et al, 2016;Ferraro, Faghri, Henning, et al, 2013;Harenstam, Palm, & Theorell, 1988;Morse, Dussetschleger, Warren et al, 2011).…”
Section: Working Conditions and Health In Prisonsmentioning
confidence: 94%
“…A large body of normative data from organisations within the public and private sector was used to develop the benchmarks. This approach has been used in a variety of occupational groups, such as police, prison officers and healthcare staff, to identify priority areas and target interventions (see Houdmont et al, 2012;Kerr et al, 2009;Kinman et al, 2016). The framework has also been incorporated into occupational health guidelines for several professional associations, including police and teaching, and in large public sector organizations such as the National Health Service.…”
Section: The Management Standard Approachmentioning
confidence: 99%
“…Most studies on burnout among correctional officers are cross-sectional studies, based on self-report questionnaires (Schaufeli & Peeters, 2000). There is a need for interventions focusing on reducing stress in correctional officers' work environment (Finney et al, 2013;Keinan & Malach-Pines, 2007;Kinman et al, 2016). Very few such interventions have been scientifically evaluated, and no such study has taken place in a Swedish setting.…”
Section: Introductionmentioning
confidence: 99%